Abstract 9301: The Association of Pulse Pressure With Brain Structure and Function in Healthy Individuals - Schumann, Andy; de la Cruz, Feliberto; Baer, Karl-Juergen (Circulation (New York, N.Y.), 2021)
IntroductionHypertension is associated to changes of structural and functional brain networks that lead to impairment of cognitive performance. Recently, pulse pressure (PP) has been suggested as cardiovascular risk factor in hypertension. HypothesisIn this study, we tested whether elevated PP is accompanied by brain structural and functional changes in healthy individuals without hypertension. MethodsWe investigated 115 healthy subjects (41±17 years, 55% females) without cardiovascular, neurological or psychiatric disorders. Structural and functional brain imaging was performed on a 3 Tesla Siemens Prisma. We assessed cognitive function using the MATRICS Consensus Cognitive Battery. Participants were categorized by PP in normal and high PP (PP>50 mmHg) according to resting blood pressure measurements in the laboratory. The normal PP group was reduced to match the high PP group with respect to age, gender, and education level. From resting functional brain images, we extracted whole-brain network connectivity between 260 independent brain regions to estimate global graph-theoretical features for integration (efficiency), resilience (assortativity), and segregation (clustering coefficient). Cortical thickness and volume were extracted from structural images using the Freesurfer image analysis suite. ResultsWhile subgroups did not differ in terms of heart rate variability, baroreflex sensitivity was decreased in the high PP group. Furthermore, subjects with high PP performed worse in the trail-making task that primarily assesses processing speed (p<0.001, FDR-corr.). Graph theoretical analyses revealed that functional brain networks in subjects with high PP were less efficient, clustered and resilient than normal PP (all p<0.001, FDR-corr.). There were no differences in brain structure between groups. However, we found a negative correlation of PP with cortical thickness in the lateral prefrontal cortex over all subjects, suggesting that high PP is associated with cortical thinning in this area (corrected for age, gender and education). ConclusionElevated PP is associated with an altered organization of functional brain networks, lower cortical thickness and decreased processing speed in healthy subjects.